The Nexus between Intellectual Capital and Islamic Bank Performance in Indonesia - Dian Juliani; M. Arsyadi Ridha (Journal of Business Management and Islamic Banking, 2024)
Research Aims: This research aims to investigate the impact of intellectual capital on the performance of Islamic Banking in Indonesia. Design/methodology/approach: The population in this research is islamic banking, type of islamic commercial banks. A purposive sampling method is used in the research. This research employs secondary data in the form of annual islamic commercial banking reports from 2017 to 2022. Multiple regression analysis was utilized. The statistical tool used to analyse the research data is eviews 12. Research Findings: This research shows that human capital efficiency and capital employed efficiency have a positive and significant effect on return on assets. Meanwhile, structural capital efficiency has a negative and significant effect on return on assets. Theoretical Contribution/Originality: This research has not been examined much because it tests the direct influence of intellectual capital efficiency using the variables human capital efficiency, structural capital efficiency, and capital employed efficiency on the performance of Islamic banking in Indonesia. Research limitation and implication: This article provides insight into Islamic banking and indicates that investing in intellectual capital has a major impact on islamic banking's the ability to generate profits. This study only examines some instances of Islamic banking in Indonesia. For further research can use islamic banking in ASEAN countries.